Assessing Oral Communication Skills In Science: A Rubric Development - Alias, Azizi; Osman, Kamisah (Penerbit Universiti Sains Malaysia, 2015)
This research was conducted to develop an analytical rubric for alternative assessment of scientific oral activities with the inculcation of 21st century skills. The aim of the research is to determine whether the developed analytical rubric is suitable for assessing oral communication skills in science activities by taking into account advice from a panel of 15 experts in science education to validate the rubric in three Delphi rounds and by using 5 experienced teachers as assessors to test the reliability of the rubric using an intra-class correlation coefficient (ICC). The study found that the analytical rubric has a high relevance percentage of 100% and high consensus of 75.0% as well as a high absolute agreement of 85.0% [ICC = .85 (95% CI, .69 to .94)]. This result shows that the analytical rubric developed is appropriate for assessing oral communication skills in school science activities. This effort is essential in realising the assessment of authentic outcomes, concurrent with 21st century needs. However, further research on the validity and reliability of the rubric is necessary.